The Influence of CEO Characteristics on Tax Aggressiveness: An Empirical Study in Indonesia - Husnaini, Wahidatul; Sasanti​, Elin Erlina; Rakhmawati, Intan; Lestari, Auliya (Universitas Nahdlatul Ulama Surabaya, 2025)
This study investigates the impact of CEO characteristics—specifically gender, age, and tenure—on corporate tax aggressiveness. The analysis utilizes a sample of 628 observations from manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023, employing OLS regression analysis with fixed effects. The results indicate that female and older CEOs are associated with significantly lower levels of tax aggressiveness, whereas CEO tenure demonstrates no statistically significant effect. Consequently, these findings offer valuable insights for policymakers and corporate boards, suggesting that promoting gender diversity in top executive positions and considering age criteria can be effective strategies for mitigating the risks associated with aggressive tax practices.